2020
DOI: 10.1186/s40662-020-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical diagnostics of the cornea

Abstract: Corneal biomechanics has been a hot topic for research in contemporary ophthalmology due to its prospective applications in diagnosis, management, and treatment of several clinical conditions, including glaucoma, elective keratorefractive surgery, and different corneal diseases. The clinical biomechanical investigation has become of great importance in the setting of refractive surgery to identify patients at higher risk of developing iatrogenic ectasia after laser vision correction. This review discusses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 90 publications
0
74
0
1
Order By: Relevance
“…Numerous studies suggest that corneal hysteresis (CH), an indicator of corneal viscoelasticity, is associated with biomechanical properties of the cornea. Some studies showed that CH may be related to the biomechanical characteristics of peripapillary sclera and lamina cribrosa, as they are embryologically developed from the mesoderm and also because the collagen fibers continue with the collagen fibers from the corneal stroma [ 1 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that corneal hysteresis (CH), an indicator of corneal viscoelasticity, is associated with biomechanical properties of the cornea. Some studies showed that CH may be related to the biomechanical characteristics of peripapillary sclera and lamina cribrosa, as they are embryologically developed from the mesoderm and also because the collagen fibers continue with the collagen fibers from the corneal stroma [ 1 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the Corvis ST is capable of analyzing the whole process of dynamic corneal deformation, it enables calculation of various dynamic corneal response (DCR) parameters [ 3 , 11 , 12 ]. Parameters including “deformation” are calculated without compensating for whole eye movement (WEM), while the parameters including “deflection” compensate for the WEM [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the moment during the cornea highest concavity (HC), parameters including radius of corneal curvature (HC radius), time from beginning to the moment of HC (HC time), maximum deformation amplitude (DA), corneal deflection area (HCDeflArea), corneal deflection amplitude (HCDeflAmp), delta arc length of the outer corneal edge between initial state and HC (HCdArclength), and distance between two corneal peaks at HC (peak distance) are measured [ 3 , 9 , 13 ]. The radius of corneal curvature at HC (curvature radius HC) and the maximum value of the integrated inverse of the corneal radius HC (InvRadMax) are also determined [ 3 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the available clinical knowledge is related to the biomechanical response to air-puff tonometry. In addition, in vivo characterization of corneal biomechanics is still influenced by the IOP level in spite of significant progress in this field 1 .…”
Section: Introductionmentioning
confidence: 99%